The Impact Of Tourism On Social Change In Indonesia - Thamrin Pawalluri (Cita konsultindo, 2023)
Thamrin Pawalluri, The expansion of Indonesia's tourism industry has unquestionably reaped economic benefits and ushered in developmental opportunities. However, beyond its undeniable economic significance, the swift growth of tourism has also left profound and lasting impacts on the nation's social fabric. The research problem focuses on understanding the impacts of tourism on the cultural traditions, customs, and habits of local communities, as well as its influence on local livelihoods, economic patterns, and social and national identities in various regions of Indonesia. In conclusion, the exploration of changes in cultural values, livelihood transformation, and local identity reveals the complex and dynamic relationship between tourism and local communities in Indonesia. Sustainable tourism development should prioritize the preservation of cultural heritage, foster diversified and resilient livelihoods, and promote genuine representations of local identities. By recognizing the multifaceted impacts of tourism on these aspects, policymakers, tourism operators, and communities can work together to create a sustainable tourism framework that respects and enhances the social fabric and cultural richness of Indonesia's diverse communities. Keywords: Impact; Tourism; Social Change.